2023
DOI: 10.1007/s11033-023-08392-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nrf2 and NF-κB pathways in diabetic wound and potential treatment strategies

Abstract: The issue of delayed wound healing or nonhealing in diabetic patients presents a challenge for modern medicine. A number of attempts have been made to understand the mechanisms behind diabetic wound. In a hyperglycemic environment, increased intracellular reactive oxygen species (ROS) disturb the balance between oxidation and antioxidant, causing the wound environment to deteriorate. It has been established that the nuclear factor E2-related factor 2 (Nrf2) and nuclear factor-kappa B (NF-κB) pathways play an i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…NF‐κb1 is a crucial transcription factor that modulates inflammatory response and oxidative stress, activating the NF‐κB signaling pathway to induce the polarization of macrophages toward M1 type. [ 40 , 41 , 42 ] Thus, the HA/TA2/KR2 treatment could reduce inflammation and oxidative stress by inhibiting NF‐κB signaling pathway, and promote the polarization of macrophages toward M2 type to an extent. More importantly, we also observed that both the key protein Stat6 and the signaling pathway of JAK‐STAT6 that mediated M2 type macrophages polarization were upregulated in the HA/TA2/KR2 group.…”
Section: Discussionmentioning
confidence: 99%
“…NF‐κb1 is a crucial transcription factor that modulates inflammatory response and oxidative stress, activating the NF‐κB signaling pathway to induce the polarization of macrophages toward M1 type. [ 40 , 41 , 42 ] Thus, the HA/TA2/KR2 treatment could reduce inflammation and oxidative stress by inhibiting NF‐κB signaling pathway, and promote the polarization of macrophages toward M2 type to an extent. More importantly, we also observed that both the key protein Stat6 and the signaling pathway of JAK‐STAT6 that mediated M2 type macrophages polarization were upregulated in the HA/TA2/KR2 group.…”
Section: Discussionmentioning
confidence: 99%